Optimization Of Salted Duck Egg Formulation With Maltodextrine In Producing Powdered Salt Duck Eggs Using The Foam-Mat Drying Method - Nurminabari, Ina Siti; Gozali, Thomas; Risdianto, Dian; Rakhmadianti, Safira; Hariadi, Hari; Rezaldi, Firman (Universitas Islam Negeri Ar-Raniry, 2025)
This study aims to produce an optimal formulation for making powdered salted duck eggs with foam-mat drying using Design Expert 13 Mixture D-Optimal method based on chemical and organoleptic properties. The use of salted duck eggs as instant seasoning is a form of product innovation to increase protein consumption in Indonesia. The research is to determine the optimal formulation of powdered salted duck eggs using the Design Expert 13 program using the Mixture D-Optimal method by analyzing protein content, moisture content, and organoleptics including color attributes, aroma attributes, taste attributes, and texture attributes (handfeel).The results of the study based on the prediction of the Design Expert 13 program showed that the optimization of the formula with a protein content of 18.04%, moisture content of 1.56%, and organoleptic values including color attributes of 4.99, aroma attributes of 4.67, taste attributes of 4.67, and texture attributes (handfeel) of 4.71. Then the accuracy value (desirability) was obtained, namely 0.761. Then, the verification results showed the protein content was 18,23%, mositure content was 3,04%, and organoleptics value include color 5,00; aroma 4,80; taste 4,67; and texture (handfeel) 4,93. The results of follow-up tests, there are fat content 30,91%; ash content 3,10%; carbohydarate content by difference method of 44,72%; and sodium (salt) content of 3,29%.